Implementasi E-Government Melalui Aplikasi Tangerang LIVE sebagai Upaya Peningkatan Good Governance di Pemerintahan Kota Tangerang - Safira Natasya (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The implementation of e-government is one of the local government's strategies in improving the quality of public services and realizing Good Governance. This study aims to analyze the implementation of e-government through the Tangerang LIVE Application as an effort to improve Good Governance in the Tangerang City Government. The research method used is a qualitative literature study approach through the search and analysis of various literature sources in the form of books, scientific journals, and official government documents related to e-government, the Tangerang LIVE Application, and the principles of Good Governance. This research analysis uses the Good Governance principles framework according to the United Nations Development Programme (UNDP), which includes transparency, participation, responsiveness, effectiveness and efficiency, and accountability. The results of the study indicate that the implementation of the Tangerang LIVE Application contributes positively to increasing public information disclosure, expanding public participation, accelerating government responses to public complaints, increasing the effectiveness and efficiency of public services, and strengthening the accountability of local government performance. However, there are several obstacles to achieving Good Governance through the Tangerang Live application and these obstacles become an evaluation of the Tangerang City government to innovate through e-government that supports the improvement of Good Governance in the Tangerang City Government. This study recommends strengthening digital literacy, improving institutional coordination, and sustainable system development to ensure optimal and inclusive e-government implementation.